Cytotoxicity of Xanthium Strumarium against Breast Cancer Cell Lines - Atheer S. Alsabah (Journal of Global Pharma Technology, 2018)
Objective: This study aimed to investigate the possible in vitro cytotoxicity of Xanthium strumarium.  Methods: The dried leaves powder was extracted with chloroform. Extract alone and combined with Doxorubicin have been evaluated by MTT assay for cytotoxicity against AMN3, AMJ13, MCF7 breast cancer cell lines and normal REF cell line.   Results: Chloroform extract has potent cytotoxicity in a dose dependent manner, against AMN3, AMJ13, MCF7 cell lines and less toxic effect on normal REF cell line; where IC50 (2.93µg/ml), (2.99µg/ml), (2.67µg/ml), and (15.84µg/ml) respectively. The cytotoxicity of extract combined with Doxorubicin showed a synergistic activity on AMN3, AMJ13, MCF7 cell lines, and dose dependent effect on normal REF cell line (synergism at 3.125-6.25µg/ml, addition at 12.5µg/ml, and antagonism at 25-100µg/ml). Conclusion: Chloroform extract has potent cytotoxicity against breast cancer cell lines and less toxic effect on normal REF cell line. In addition to synergistic activity in combination with Doxorubicin on breast cancer cell lines and dose dependent effect on REF cell line.  Keywords: Chloroform extract, Xanthium strumarium, Cytotoxicity, MTT assay, cell line.